2020
DOI: 10.1080/21645515.2020.1818519
|View full text |Cite
|
Sign up to set email alerts
|

The role of the thymus in COVID-19 disease severity: implications for antibody treatment and immunization

Abstract: The thymus is a largely neglected organ but plays a significant role in the regulation of adaptive immune responses. The effect of aging on the thymus and immune senescence is well established, and the resulting inflammaging is found to be implicated in the development of many chronic diseases including atherosclerosis, hypertension and type 2 diabetes. Both aging and diseases of inflammaging are associated with severe COVID-19 disease, and a dysfunctional thymus may be a predisposing factor. In addition, insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 77 publications
(109 reference statements)
1
33
0
2
Order By: Relevance
“…The effect of aging on the thymus and immune senescence is well established, and the resulting inflammaging is found to be implicated in the development of many chronic diseases (Gunes et al, 2020;Kellogg and Equils, 2020). Both aging and diseases of inflammaging are associated with severe COVID-19, and a dysfunctional thymus may be implicated in the unfavorable outcome of disease (Gunes et al, 2020;Kellogg and Equils, 2020). Of note, MX1 plays an important role in the thymus as part of the innate antiviral immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of aging on the thymus and immune senescence is well established, and the resulting inflammaging is found to be implicated in the development of many chronic diseases (Gunes et al, 2020;Kellogg and Equils, 2020). Both aging and diseases of inflammaging are associated with severe COVID-19, and a dysfunctional thymus may be implicated in the unfavorable outcome of disease (Gunes et al, 2020;Kellogg and Equils, 2020). Of note, MX1 plays an important role in the thymus as part of the innate antiviral immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of aging on the thymus and immune senescence is well established, and the resulting inflammaging is found to be implicated in the development of many chronic diseases. Both aging and diseases of inflammaging are associated with severe COVID-19, and a dysfunctional thymus may be implicated in the unfavorable outcome of disease (19, 20). Thus, our finding suggests that the identified SNPs could be severe COVID-19 risk factors also for their implications in the thymus function.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our investigations have shown that in mice with thymic involution, there was increased lymphocyte infiltration into self-tissues, including the lung [ 67 ]. Although there is increasing interest in the correlation between immunosenescence and the increased risk of COVID-19 mortality in the elderly, more research is needed to fully elucidate the role of pre-existing lung inflammation and infiltration of potentially self-reactive T cells during COVID-19 pathogenesis [ 73 , 74 , 75 , 76 ].…”
Section: How Does Age-related Thymic Involution and Subsequent T-cmentioning
confidence: 99%
“…Currently there are several proposed immune interventions for rebooting anti-COVID-19 immunity mostly focused on enhancing T effector cell responses and ameliorating immune cell-induced cytokine storm [ 15 , 87 ], which is more deadly in the elderly. Given that there appears to be profound T cell dysfunction in severe, particularly in aged, COVID-19 cases [ 32 , 88 , 89 ], rebooting T cell function by restoring thymic function should be considered as a potential holistic treatment for improving antiviral immunity and vaccination efficiency and potentially improve COVID-19 prognosis [ 76 ]. Along with rejuvenation of aged thymic function, refreshing the peripheral senescent T cell system, enhancing immune homeostasis, and reducing chronic peripheral inflammation, is also important for boosting antiviral immunity and vaccination efficiency [ 3 , 17 , 18 ].…”
Section: How Can We Sufficiently Restore Antiviral Immunity and Immentioning
confidence: 99%